Mapping Alternative Qur'ānic Hermeneutics: The Case of Majlis Tarbiyyah Garut - Yusuf Burhanuddin; Mustaffa Abdullah (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the approach to Qur'āniyyūn interpretation and doctrine at Majlis Tarbiyyah (MTb) Garut, which holds that the Qur'ān is the sole source of Islamic law and rejects the authority of hadith. Historically, Qur'āniyyūn ideas in Indonesia overlap with the Inkar Sunnah movement and the Indonesian Islamic State (NII) network, despite being formally banned. This study highlights the continuity and transformation of these thoughts in the contemporary context through an exclusive interpretation methodology developed by MTb. Using a qualitative approach grounded in literature reviews, interviews, and observations, this study examines the primary texts of Qur'āniyyūn figures and related secondary sources. The analysis focuses on the construction of interpretations of Qur'ānic verses into doctrines, including the conception of the Torah School, and on the possibility of renewing these ideas in light of the thoughts of previous Qur'anic scholars in Indonesia. This study contributes to mapping the dynamics of alternative interpretations in modern Islamic society.